The impact of China’s green credit policy on the innovation of manufacturing enterprises - Guanglin Sun; Qinyao Feng; Shanshan Wu; Chuanxin Xia (Journal of Innovation & Knowledge)
This study empirically investigated the effects of green credit policies on corporate innovation in China, utilizing panel data for A-share listed manufacturing companies from 2008 to 2022. The analysis employed double-difference models, with the 2012 introduction of the Green Credit Guidelines treated as an exogenous shock. Green credit schemes were found to restrict innovation among more heavily-polluting enterprises. In terms of mechanisms, financial constraint effects outweighed the Porter effect, with heightened financial limitations imposed by green credit schemes driving the observed decrease in corporate innovation. Additionally, the degree of local financial development was found to strongly mediate how green credit policies impacted innovation-related investments, while government subsidies and internal investment levels exacerbated the negative effects of green credit schemes on innovation. Green credit-related declines in innovation within heavily polluting industries were exaggerated for privately owned versus state-owned enterprises. Similarly, technology-intensive enterprises, those operating in highly competitive markets, and those less-dependent on human labor also experienced greater reductions in innovation. Finally, green credit-related declines in innovation were most severe for enterprises located in the Central Region of China.